STUDY REGARDING THE UPPER LIMB RANGE OF MOTION AFTER BREAST CANCER SURGERY - Oana Maria BALTAG; Mihaela APOSTU; Mariana CORDUN (Cluj University Press, 2022)
Introduction: Mastectomy surgery in association with local radiotherapy and chemotherapy generates side effects such as: lymphedema, decreased range of motion, chronic pain, cardiotoxicity, neuropathy, premature menopause, infertility, anxiety, depression, fatigue. Decreased range of motion is the most disabling side effect of the treatment. Aerobic and resistive exercises can prevent lymphedema and improve the range of motion of the upper limb on the side of mastectomy. Objective: The purpose of the present study is to verify the effectiveness of an individualized kinetic program, applied to improve the upper limb range of motion after breast cancer surgery. Methods: In this study, 5 subjects (females, aged between 49 and 67) with right radical mastectomy and axillary lympho-dissection were included. They performed a kinetic program twice a week for 6 months and we evaluated the range motion at the level of the upper limb. Results: All the movements performed in upper limb (flexion, extension, abduction, adduction, internal and external rotation) improved, suggesting that the kinetic program is efficient. The average of the flexion movement increased by 35°, from 126° to 161°. The values obtained for the extension movement show an increase of the average by 14.6°. The abduction movement improved from 120° to 170°. At the elbow level, the flexion increased by 24.4° and the extension decreased by 6°. At the wrist level, the flexion increased by 37.4° and the extension increased from 41.8° to 78°. Conclusions: After applying the therapeutic program, the final physical assessments highlights that the range of motion increased in the upper limb. Article history: Received 2022 October 17; Revised 2022 October 20; Accepted 2022 October 21; Available online 2022 November 20; Available print 2022 December 20. REZUMAT. Studiu privind amplitudinea de mișcare a membrului superior după intervenția chirurgicală în cancerul de sân. Introducere: Intervenția de mastectomie asociată cu radioterapia locală și chimioterapia generează efecte secundare cum ar fi: limfedem, amplitudine de mișcare scăzută, durere cronică, cardiotoxicitate, neuropatie, menopauză prematură, infertilitate, anxietate, depresie, oboseală. Amplitudinea de mișcare diminuată este cel mai dăunător efect secundar al tratamentului. Obiective: Scopul prezentului studiu este de a verifica eficiența unui program kinetic individualizat, aplicat pentru a îmbunătăți amplitudinea mișcărilor membrului superior după intervenția chirurgicală în cancerul de sân. Metode: În acest studiu au fost incluși 5 subiecți (de gen feminin, cu vârsta cuprinsă între 49 și 67 de ani) cu mastectomie radicală dreaptă și limfodisecție axilară. Rezultate: Toate mișcările efectuate la nivelul membrului superior (flexie, extensie, abducție, adducție, rotație internă și externă) s-au îmbunătățit, sugerând că programul kinetic este eficient. Media mișcării de flexie a crescut cu 35°, de la 126° la 161°. Valorile obținute pentru mișcarea de extensie arată o creștere a mediei cu 14.6°. Mișcarea de adducție s-a îmbunătățit de la 120° la 170°. La nivelul cotului, flexia a crescut cu 24.4° și extensia a scăzut cu 6°. La nivelul mâinii, flexia a crescut cu 24.4° și extensia s-a îmbunătățit de la 41.8° la 78°. Concluzii: După aplicarea programului terapeutic, evaluare finală evidențiază că amplitudinea mișcărilor membrului superior s-a îmbunătățit. Cuvinte cheie: cancer de sân, amplitudine de mișcare, mastectomie.